Camarines Sur assessment of the bottom-up budgeting process for FY 2016 - Cleofe S. Pastrana; Marites B. Lagarto (Philippine Institute for Development Studies (PIDS), 2016)
Bottom-up budgeting (BUB) is a mechanism implemented to institutionalize and incentivize grassroots participation, as represented by civil society organizations, in the planning and budgeting of their respective cities or municipalities. This paper assesses how the various participatory steps were conducted and how the selected subprojects from the previous budgeting round was being implemented. Specifically, this paper focuses on three local government units in Camarines Sur, with various levels of development and participation in government programs. The assessment was conducted by observing the BUB activities of the study sites, conducting interviews and focus group discussions, and validating findings against secondary data. Findings on the general usefulness of the BUB, its current guidelines, and interaction with corollary government programs were highlighted, along with recommendations.
Keywords: 330; Philippines; Camarines Sur; bottom-up budgeting; poverty reduction; local governance; participatory budgeting; civil society organizations; grassroots